ADVERSITY QUOTIENT-PARENTING: A NARRATIVE STUDY OF THE EMOTIONAL SUPPORT AND PSYCHOLOGICAL STATE OF CHILDREN LEFT BEHIND BY THEIR PARENTS AS INDONESIAN MIGRANT WORKERS (TKI) - Adawiyah, Zaidatul; Sujadi, Eko (LP2M IAI Al-Khairat Pamekasan, 2025)
The phenomenon of Indonesian migrant workers (TKI) for the Indonesian people reflects an effort to improve the family's economic level. However, children without parental figures will experience complex psychological consequences. This study aims to investigate the extent of the influence of adversity quotient parenting to analyze the psychological conditions of children whose parents work as TKI. The research method used is a narrative qualitative design involving three informants of children whose parents are migrant workers. Data were collected through in-depth interviews in several sessions and analyzed using thematic analysis. The main findings show that children who are able to manage their emotions and remain resilient under pressure demonstrate active engagement in the four dimensions of AQ. The child's ability to calm down and maintain emotional stability reflects the control dimension. The origin & ownership dimension is reflected in the attitude of not blaming circumstances but rather taking responsibility for personal responses. The reach dimension is seen when children can limit the impact of difficulties so that they do not interfere with other aspects of their lives. Meanwhile, the endurance dimension is manifested in their optimism that difficult situations are temporary. Nevertheless, some children still experience psychological distress but can overcome it with the right support. This study has implications related to handling the psychology of children whose parents work as migrant workers. There is a need for family counseling services for parents, guardians, and children regarding the adversity quotient-parenting awareness as a provision and readiness before leaving them to work abroad.